2021
DOI: 10.21083/ajote.v10i1.6554
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Amidst COVID-19 Emergency: A Case of the University of Malawi’s School of Education

Abstract: This paper explores faculty members’ concerns and level of preparedness for open and distance learning (ODL) at the University of Malawi’s School of Education during the recent Covid-19 pandemic within a context that considers ODL as a means of mitigating the impact of the pandemic on teaching and learning. Data were gathered through semi-structured interviews with four experienced academic leaders within the school of education. The Concerns Based Adoption Model (CBAM), particularly stages of concerns, served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The implications for symbolic politics were demonstrated in events for COVID-19 lockdown and public demonstrations. Other scholars have noted that the COVID-19 pandemic was also driving digital transformation in societies (Maseko, Gondwe, Winiko & Chiziwa, 2021;Munthali, George & Xuelian, 2020). The findings showed that the government was compelled to consider the reduction of the cost of Internet data because it had implemented the COVID-19 lockdown and was required to support the use of ICTs.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The implications for symbolic politics were demonstrated in events for COVID-19 lockdown and public demonstrations. Other scholars have noted that the COVID-19 pandemic was also driving digital transformation in societies (Maseko, Gondwe, Winiko & Chiziwa, 2021;Munthali, George & Xuelian, 2020). The findings showed that the government was compelled to consider the reduction of the cost of Internet data because it had implemented the COVID-19 lockdown and was required to support the use of ICTs.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…One of contributing factors could be rising of transit capacity costs which service providers in landlocked countries like Malawi incur (A4AI, 2021). Discussions on the recent causes high cost of internet services are missing in literature despite other studies mentioning the issue of internet cost (Bichler, 2008b;Maseko, Gondwe, Winiko & Chiziwa, 2021). To the knowledge of the author, studies that have analysed internet cost in detail and how public discussions influence government policies and telecommunication sector regulations are missing.…”
Section: State Of Affordability Driversmentioning
confidence: 99%
See 2 more Smart Citations